Distinct gene reprogramming in rosetted and symptomless shoots from the same mature rose plants infected with rose rosette virus - Mutethia, Reghan; Hosain, Shakil; Herath, Venura; Ong, Kevin; Riera-Lizarazu, Oscar; Byrne, David; Kolomiets, Michael V.; Berg-Falloure, Katherine M.; Floyd, Jeff; Verchot, Jeanmarie (Frontiers in Plant Science, 2025)
Rose rosette virus (RRV) causes disease in rose shrubs manifesting as abnormal branch growth, stem thickening, increased thorniness, as well as malformed, discolored leaves and flowers. The uneven and strange development near apical regions and only in parts of the plant led us to investigate how RRV influences growth promoters to alter internal developmental programs. Leaf samples were collected from symptomatic (rosetted) and asymptomatic shoots of the same rose plants. We quantified viral RNA levels and analyzed the concentrations of some key hormones (abscisic acid [ABA], caffeic acid [CFA], indole acetic acid [IAA], and gibberellin [GA]). Additionally, gene expression profiling was performed, focusing on genes involved in hormone synthesis and signaling, auxin transport, and plant development. Viral RNA levels were unevenly distributed between rosetted and non-rosetted tissues. The ABA and IAA levels were similar between tissue types, whereas CFA and GA exhibited marked differences. We identified 39 genes with distinct or opposite expression in rosetted versus asymptomatic tissues, including PILS3, PIN1, and two SAUR genes related to auxin transport and response. Expression of key regulators of ABA and GA synthesis and signaling, including YUCCA and AUX/IAA genes, were altered. Notably, Lonely Guy 3 (LOG3), which encodes a cytokinin-acitvating enzyme implicated in leaf patterning was significantly reduced in rosetted leaves, suggesting leaf-specific hormone imbalances. Several WOX transcription factors were suppressed indicating a potential role in antiviral responses. Our findings demonstrate that RRV selectively alters hormonal profiles and gene expression involved in plant growth and development. This study identified precise incursions of RRV into host molecular mechanisms controlling plant development and growth.